2012
DOI: 10.1007/s11657-012-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone health status of premenopausal healthy adult females in Pakistani females

Abstract: Bone turnover is high with high prevalence of vitamin D deficiency in apparently healthy premenopausal females predisposing them to higher risk for development of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“… Mean25OHD (nmol/L) a Reference values of vitamin D status Kanani et al 2013 [ 13 ] Karachi, Pakistan Female medical students of Public hospital. 84 15 ± 10.71 25OHD < 25 nmol/L in 96.4% < 75 nmol/L in 98.8% Dar et al 2012 [ 14 ] Karachi, Pakistan Pre-menopausal volunteers 174 38.3 ± 15.23 25OHD < 75 nmol/L in 98.9% Sharif et al 2013 [ 15 ] Lahore, Pakistan Pregnant Lactating women 40 40 26.5 ± 17.1 21.4 ± 16.3 25OHD < 50 nmol/L in 95% 25OHD < 50 nmol/L in 97.5% Aslam et al 2012 [ 16 ] Faisalabad, Pakistan Pregnant women 61 NA 25OHD < 75 nmol/L in 97% Junaid et al 2015 [ 24 ] Lahore, Pakistan Child bearing age working women 215 40.4 ± 34.45 25OHD < 50 nmol/L in 73% 25OHD < 75 nmol/L in 90% Kaykhaei et al 2011 [ 25 ] Zahedan, Iran Adult males 431 Adult females 562 993 34.3 ± 29.43 25OHD < 75 nmol/L in 94.7% Sharma et al 2016 [ 26 ] Delhi, India Pregnant women 418 38.5 ± 22.39 25OHD < 80 nmol/L in 93.5% Salameh et al 2016 [ 27 ] Doha, Qatar Exclusively breast-feeding mothers 60 NA 25OHD < 50 nmol/L in 78% Ullah et al 2013 [ 28 ] Dhaka, Bangladesh Pregnant women 188 61.2 ± 1.78 25OHD < 75 nmol/L in 78% Haugen et al 2016 [ 29 ] Kathmando, Nepal Nursing mothers 500 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Mean25OHD (nmol/L) a Reference values of vitamin D status Kanani et al 2013 [ 13 ] Karachi, Pakistan Female medical students of Public hospital. 84 15 ± 10.71 25OHD < 25 nmol/L in 96.4% < 75 nmol/L in 98.8% Dar et al 2012 [ 14 ] Karachi, Pakistan Pre-menopausal volunteers 174 38.3 ± 15.23 25OHD < 75 nmol/L in 98.9% Sharif et al 2013 [ 15 ] Lahore, Pakistan Pregnant Lactating women 40 40 26.5 ± 17.1 21.4 ± 16.3 25OHD < 50 nmol/L in 95% 25OHD < 50 nmol/L in 97.5% Aslam et al 2012 [ 16 ] Faisalabad, Pakistan Pregnant women 61 NA 25OHD < 75 nmol/L in 97% Junaid et al 2015 [ 24 ] Lahore, Pakistan Child bearing age working women 215 40.4 ± 34.45 25OHD < 50 nmol/L in 73% 25OHD < 75 nmol/L in 90% Kaykhaei et al 2011 [ 25 ] Zahedan, Iran Adult males 431 Adult females 562 993 34.3 ± 29.43 25OHD < 75 nmol/L in 94.7% Sharma et al 2016 [ 26 ] Delhi, India Pregnant women 418 38.5 ± 22.39 25OHD < 80 nmol/L in 93.5% Salameh et al 2016 [ 27 ] Doha, Qatar Exclusively breast-feeding mothers 60 NA 25OHD < 50 nmol/L in 78% Ullah et al 2013 [ 28 ] Dhaka, Bangladesh Pregnant women 188 61.2 ± 1.78 25OHD < 75 nmol/L in 78% Haugen et al 2016 [ 29 ] Kathmando, Nepal Nursing mothers 500 …”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan the 25OHD levels have been found to be very low in various women populations e.g. 98.8% in female medical students of public sector hospital [ 13 ], 98.9% in premenopausal volunteers [ 14 ] and over 97% in pregnant women [ 15 , 16 ]. The nursing mothers have been out of focus as a specific study group and there are no reports of 25OHD status in women of southern Punjab.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies did not mention demographic areas (urban/rural) for study population, 4 studies were conducted among urban populations and two studies included both rural and urban populations. Socio economic status for study participants was not mentioned in most of the studies, 8 studies were conducted on both lower and upper socio-economic groups of population and only one study was conducted on lower class population [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. The weighted mean level of vitamin D for study participants was 17.93ng/mL (weighted SD 8.24 ng/mL) [Mean vitamin D level ranged from 8.44 ng/mL to 32ng/mL] and random effect meta-analysis showed that the weighted pooled prevalence of vitamin D de ciency was 73% [95% CI: 63% to 83%] with high degree of heterogeneity (I 2 = 98.20%; p =0.00).…”
Section: Indiamentioning
confidence: 99%
“…According to WHO criteria, individuals with BMD T-scores < -2.5 are osteoporotic and the ones between < -2.5 and -1 are at a high risk of developing osteoporosis, while T-scores > -1 are considered to be normal [2]. Our study depicts increased bone resorption in osteopenic subjects as suggested by the low BMD and high CTx levels [22]. CTx being an authentic bone resorption marker suggests that the bone is having osteoclastic activity going on for the release of minerals like calcium in the blood [23].…”
Section: Discussionmentioning
confidence: 68%